Inorganic chemistry for dummies - Matson, Michael L.; Orbaek, Alvin W. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
Book Description: The easy way to get a grip on inorganic chemistry. Inorganic chemistry can be an intimidating subject, but it doesn't have to be! Whether you're currently enrolled in an inorganic chemistry class or you have a background in chemistry and want to expand your knowledge, Inorganic Chemistry For Dummies is the approachable, hands-on guide you can trust for fast, easy learning. Inorganic Chemistry For Dummies features a thorough introduction to the study of the synthesis and behavior of inorganic and organometallic compounds. In plain English, it explains the principles of inorganic chemistry and includes worked-out problems to enhance your understanding of the key theories and concepts of the field. Presents information in an effective and straightforward manner; - Covers topics you'll encounter in a typical inorganic chemistry course; - Provides plain-English explanations of complicated concepts. If you're pursuing a career as a nurse, doctor, or engineer or a lifelong learner looking to make sense of this fascinating subject, Inorganic Chemistry For Dummies is the quick and painless way to master inorganic chemistry.
Includes index.
PHR
Keywords: Chemistry, Inorganic; Pharmacy